HIV transmission risk among serodiscordant couples: a retrospective study of former plasma donors in Henan, China - Lu, Wang; Zeng, Ge; Luo, Jing; Duo, Shan; Xing, Gao; Guo-Wei, Ding; Jian-Ping, Zhou; Wen-Sheng, He; Ning, Wang (Journal of acquired immune deficiency syndromes (1999), 2010)
OBJECTIVES: To estimate the HIV incidence and assess the behavioral, clinical, and quality-of-life risk factors for HIV transmission among serodiscordant couples from Henan Province, China. METHODS: Between January 2006 and December 2008, initially seronegative spouses were tested for HIV at six month intervals. Retrospectively identified subjects were interviewed through face-to-face questionnaire. Cox proportional-hazards model was used to assess the relationship between risk factors and HIV seroconversion. RESULTS: Out of 1927 couples, 84 (4.3%) seroconversions occurred, representing a seroconversion rate of 1.71 per 100 person-years. Seroconversion rates increased over time. Not always using condoms (RR=8.42; 95% CI, 4.83-14.67), sexual activity ≥ 4 times per month (RR=5.24; 95% CI, 2.55-10.77), not switching anti-retroviral treatment regimen (RR=1.99; 95% CI, 0.85-4.65), and a quality of life score <12 on the psychological domain (RR=2.33; 95% CI, 1.21-4.48) were associated with increased risk of seroconversion. Seventy one percent of index spouses were on ART. There was no association between rate of HIV seroconversion and last recorded CD4 cell count level of the index spouse. CONCLUSIONS: Effective HIV prevention interventions targeting discordant couples should focus on sustaining health education, increasing psychosocial support services, and increasing medication adherence monitoring.